IL-2-Agonist-Induced IFN-γ Exacerbates Systemic Anaphylaxis in Food Allergen-Sensitized Mice - Link, Christopher W.M.; Rau, Christina N.; Udoye, Christopher C.; Ragab, Mohab; Korkmaz, Rabia Ü.; Comdühr, Sara; Clauder, Ann-Katrin; Lindemann, Timo; Frehse, Britta; Hofmann, Katharina; Almeida, Larissa N.; Laumonnier, Yves; et al. (Frontiers in Immunology, 2020)
Food allergies are common, costly and potentially life-threatening disorders. They are driven by Th2, but inhibited by Th1 reactions. There is also evidence indicating that IL-2 agonist treatment inhibits allergic sensitization through expansion of regulatory T cells. Here, we tested the impact of an IL-2 agonist in a novel model for food allergy to hen´s egg in mice sensitized without artificial adjuvants. Prophylactic IL-2 agonist treatment expanded Treg populations and inhibited allergen-specific sensitization. However, IL-2 agonist treatment of already sensitized mice increased mast cell responses and allergic anaphylaxis upon allergen re-challenge. These effects depended on allergen-specific IgE and were mediated through IFN-g, as shown by IgE transfer and blockade of IFN-g with monoclonal antibodies. These results suggest that although shifting the allergic reaction towards a Treg/Th1 response inhibits allergic sensitization, the prototypic Th1 cytokine IFN-g promotes mast cell activation and allergen-induced anaphylaxis in individuals that are already IgE-sensitized. Hence, while a Th1 response can prevent the development of food allergy, IFN-g has the ability to exacerbate already established food allergy.